Mentoring and Training for the PPDB Process to Improve School Administration Services at SMK Bina Jaya Palembang - Indah Rahma Sari; Amelia Anggraini; Bella Paramita; Anggoro Aryo Pramuditho; Ibnu Aqil (Mauve Journal De Leardu, 2025)
The New Student Admission Process (PPDB) is an important stage in maintaining the quality and integrity of educational institutions. This article discusses the implementation of socialization and training carried out at SMK Bina Jaya Palembang to increase the competence of the PPDB committee in carrying out its duties effectively and transparently. This activity aims to provide an understanding of PPDB procedures, strengthen the committee's technical skills, and ensure the process runs according to established operational standards. The methods used in this activity include delivering material, practical simulations, and group discussions to improve team coordination. The results of the activity showed an increase in the committee's understanding regarding PPDB stages, implementation of digital systems, and ability to handle administrative obstacles. This socialization also has a positive impact on creating a more structured, transparent and accountable PPDB process. By carrying out this activity, it is hoped that SMK Bina Jaya Palembang can strengthen public confidence in a more professional and quality admissions system for new students.